Catalytically inactivated angiotensin converting enzyme 2 (ACE2) variants and uses thereof - LIU SHENGJIANG (2023)
Angiotensin converting enzyme 2 (ACE2) as a specific receptor for several beta-group coronaviruses, including severe respiratory syndrome (SARS) coronavirus (SARS-CoV-1), as well as a pathogenic agent for the low pathogenic coronaviruses of CoVID-19, SARS-CoV-2 and HCoV-NL63, which recently cause world pandemic, is a member of the alpha-coronavirus group. The viral spike protein (S) of the viral envelope is identified to bind to ACE2 as a viral receptor to initiate the viral replication cycle. The present invention provides ACE2 and mutants or variants thereof, viral or non-viral vectors thereof, as well as methods of treating a viral infection in a human subject by using such mutants or variants. 血管紧张素转化酶2（ACE2）作为几种β基团冠状病毒的特异性受体，包括严重呼吸综合征（SARS）冠状病毒（SARS-CoV-1），以及最近引起世界大流行的CoVID-19、SARS-CoV-2和HCoV-NL63的低致病性冠状病毒的致病剂，是α-冠状病毒组中的成员。确认病毒包膜的病毒刺突蛋白(S)以结合ACE2作为病毒受体以启动病毒复制周期。本发明提供ACE2及其突变体或变体、其病毒或非病毒载体，还提供了通过使用此类突变体或变体治疗人类受试者的病毒感染的方法。